CT FINDINGS IN PATIENTS WITH HEAD INJURY AT A TEACHING HOSPITAL IN NIGERIA - Ahidjo A; Minoza K; Abba A.A; Usman A.U; Namba S.I; Okedayo M; Charles D (Ntec Specialist, 2016)
Background: There is paucity of data on computed tomography findings in head injury patients from this part of Africa inspite of the high number of trauma cases seen. Objectives: The objective of this study was to determine the pattern of findings on Computed Tomography (CT) scan of the head in patients with head injury in our locality, with the aim of detecting the pitfalls to help make improvements. Material: Seventy-eight patients with head injury, who had CT scan of the head conducted in the Radiology department, University of Maiduguri Teaching Hospital between September 2011 to December 2013 were retrospectively reviewed by two Radiology residents and a Consultant Radiologist. Data was retrieved from the CT record book in that unit. Results: Head injury sustained as a result of road traffic accident (RTA) is the most frequent indication for CT head imaging in our study, with the lowest coming from request in bomb blast patients. Linear skull fractures were the most frequent finding, while rupture of the globe and frontal sinomucoceole, amongst others were the least. Gender variation showed that males were four times more affected than females and the age range of patients was 9 - 70 years. Conclusion: RTA was the most common cause of head injury for which request for CT scan was made, and linear skull fractures were the most frequent finding. Males between 20-40 years were the most affected. CT is the most efficient imaging tool for detection of injuries in acute cases